Solvent Extraction of Pr and Nd from Chloride Solution by Mixtures of Acidic Extractants and LIX 63 - Lee, Man Seung; Liu, Yang; Jeon, Ho Seok (Korean Journal of Metals and Materials, 2016)
Mixtures of acidic extractants and LIX 63 were employed to improve the extraction efficiency of Pr and Nd from chloride solutions. The effect of the composition of the extractant mixtures has been studied. The order of metal extraction by single acidic extractant was D2EHPA > PC88A > Cyanex 272 > Cyanex 301. The addition of LIX 63 to the acidic extractants resulted in a synergistic effect, and the strength of the effect was the reverse order of that found for extraction by single extractants. Moreover, mixing of saponified Cyanex 272 and LIX 63 enhanced the extraction, while the addition of Alamine 336 to the mixtures of Cyanex 272 and LIX 63 depressed the extraction. KCI Citation Count: 17